The structure of hair thickness distribution over women's heads surface - Šimková, Lucie; Skřontová, Marie; Jelen, Pavel; Zeman, Josef (Acta Universitatis Carolinae. Kinanthropologica, 2012)
The article encompasses a possible concept of description of the structure of hair thickness distribution over women's heads. It is based on real data realized in Caucasian population and results in the necessity of introduction of several type groups of women's heads coverage. With an example included, it eliminates the possibility of the distribution to be random and that there are all of the possibilities of the distribution realized in the population, as well as that it could be reasonable to average these distinct type groups and look for the mean distribution in the population. The distribution structure is most likely contingent on genetics and is entrenched in some part of the DNA; it is not yet clear however, what intra-species advantages particular structure types could yield, while the correlation of the particular distributions with types of humans is subject to current research.
Keywords: antropometrie; Anthropometry; Female; statistika jako téma; Microscopy; Head; mikroskopie; Statistics as Topic; Humans; vlasy, chlupy; Hair; Scalp; genetické jevy; běloši; lidé; skalp; ženské pohlaví; White People; Genetic Phenomena; hlava; Human Experimentation; experimenty na lidech